2000
DOI: 10.1002/1522-2675(20000809)83:8<1711::aid-hlca1711>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Switching: A Fully Reversible, Optically Active Photochemical Switch Based on a Tetraethynylethene‐1,1′‐Binaphthalene Hybrid System

Abstract: Dedicated to Prof. Albert Eschenmoser on the occasion of his 75th birthdayThe synthesis, characterization, and physical properties of a novel, fully reversible, light-driven molecular switch, (R,R)-1/(R,R)-2, based on a tetraethynylethene-1,1'-binaphthalene hybrid system are presented. trans-Configured (R,R)-1 was synthesized in 57% yield by Stille cross-coupling between stannylated tetraethynylethene 3 and 3-iodo-1,1'-binaphthalene derivative (R)-4 (cf. Scheme 2). The cis-isomer (R,R)-2 was prepared from (R,R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…The synthesis of ( R )‐ 13 started from alkyne ( R )‐ 15 , which was prepared from ( R )‐1,1′‐bi(2,2′‐naphthol) [( R )‐BINOL] according to a published procedure 31,32. Oxidative Hay coupling with an excess of prop‐2‐yn‐1‐ol provided alcohol ( R )‐ 16 in 51 % yield together with buta‐1,3‐diyne ( R , R )‐ 17 (18 %, Scheme ), formed by homo‐coupling of ( R )‐ 15 .…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of ( R )‐ 13 started from alkyne ( R )‐ 15 , which was prepared from ( R )‐1,1′‐bi(2,2′‐naphthol) [( R )‐BINOL] according to a published procedure 31,32. Oxidative Hay coupling with an excess of prop‐2‐yn‐1‐ol provided alcohol ( R )‐ 16 in 51 % yield together with buta‐1,3‐diyne ( R , R )‐ 17 (18 %, Scheme ), formed by homo‐coupling of ( R )‐ 15 .…”
Section: Resultsmentioning
confidence: 99%
“…All of the compounds exhibited slight blueshifts in their π–π* and CT bands in the Z forms (Figure 4). It has been reported that ethynylethene derivatives without steric hindrance do not display such blueshifts upon E ‐to‐ Z isomerization 8c. d Figure 5 shows the optimized structures of ( E )‐ 4 and ( Z )‐ 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Saalfrank et al [182] allowed stannylalkynes or bis(trimethylstannyl)alkyne to react with bromoallenes to afford conjugated alkynylallenes or diastereomeric ynediallenes. Diederich et al [183] synthesized a novel light-driven fully reversible molecular switch by a cross-coupling between a stannylated tetraethynylethene and a 3-iodo-1,1 -binaphthyl derivative (Scheme 6.43).…”
Section: Couplings Of Alkynyltinsmentioning
confidence: 99%